A new kinetic model for Ni(II) ion flotation based on gene expression programming. Issue 15 (13th October 2019) - Hoseinian, Fatemeh Sadat; Rezai, Bahram; Kowsari, Elaheh
ABSTRACT: The Ni(II) ion flotation kinetics with sodium dodecylsulfate as collector was studied with the aim of developing new models to predict the flotation rate constant (k) of Ni(II) ions and water removal during the process of Ni(II) ion flotation. In this regard, the most influential parameters on Ni(II) ion flotation efficiency including the ratio of collector concentration on the Ni(II) ion concentration, impeller speed, activity coefficient, and pH were used to develop predictive models. The results show that the proposed gene expression programming models can be used to predict the flotation rate constant of Ni(II) ions and water removal.